The role of formal models in theory building: an application to strategy theory. - Phelps, Bob (Cranfield University, 2003)
A problem of the management field is that concepts are often vague and this breeds fragmented theories, each concentrating on different aspects of an underlying issue. This paper proposes the development of formal models in management to clarify and integrate the issues of the field. It illustrates this approach with a model of competitive advantage.